Skills in person-centred counselling & psychotherapy - Tolan, Janet, 1954- (London : SAGE, 2012)
"This book has already helped thousands of beginning practitioners understand the subtleties of the person-centred approach and develop skills in person-centred counseling practice. Now in its Second Edition, this step-by-step guide takes the reader through the counseling process, providing advice on how to structure and manage therapeutic work in ways which are thoroughly grounded in person-centred principles. Janet Tolan defines the key tenets of the approach - psychological contact, congruence, empathy and unconditional positive regard - and demonstrates how they are used effectively in a range of counsellor-client interactions. Describing all aspects of the therapeutic relationship from the initial meeting to ending the relationship well, this new edition contains new chapters - Debates & Developments in Person-Centred Practice and Edgy and Ethical Issues. This book is an ideal introduction for beginners and for more experienced therapists who want to extend their range."--Publisher's website.
Ch. 1. The Theoretical Framework -- Ch. 2. Empathy -- Ch. 3. Empathic Understanding -- Ch. 4. Congruence -- Ch. 5. Congruence in Practice -- Ch. 6. Unconditional Positive Regard -- Ch. 7. Psychological Contact-Basic and Cognitive Contact (Rose Cameron) -- Ch. 8. Psychological Contact- Subtle Contact (Rose Cameron) -- Ch. 9. The Therapeutic Process -- Ch. 10. Beginnings and Endings -- Ch. 11. Professional Issues -- Ch. 12. Managing the Work in an Organisation -- Ch. 13. Edgy and Ethical Issues (Janet Tolan and Rose Cameron) -- Ch. 14. Debates and Development in Practice (Rose Cameron).
Includes bibliographical references and index.
Keywords: Client-centered psychotherapy; Counseling; Nondirective Therapy; Counseling -- methods; Professional-Patient Relations; Health and Fitness; Client-centered psychotherapy; Counseling